The Influence of Financial Attitudes, Financial Literacy, and Education Levels on Financial Behavior in MSMEs in Buleleng District. - Luh Kartika Ningsih; Kadek Wina Nariani; Ni Kadek Ayu Trisnadewi; Nazima (Yayasan Riset dan Pengembangan Intelektual, 2023)
In economic development, MSMEs have a significant contribution. However, in its development there are certainly problems. It is important to apply financial attitudes in financial management to create good financial behavior. To be able to have a good financial attitude requires basic financial knowledge which can be obtained from financial literacy. Broad financial literacy can be obtained through the education level of the MSME players themselves. The aim of this research is to determine the influence of financial attitudes, financial literacy, and level of education on financial behavior in MSMEs in Buleleng Regency. The sampling technique in this study used a simple random sampling technique by determining the number of samples using the Slovin formula. The analysis techniques used in this research are the Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination, and Statistical Analysis of the t test. The research results prove that 1). Financial Attitude has a positive and insignificant effect on the Financial Behavior of MSMEs in Buleleng Regency. 2). Financial Literacy has a significant positive effect on Financial Behavior among MSMEs in Buleleng Regency. 3). The level of education has a significant positive effect on the financial behavior of MSMEs in Buleleng Regency.